Internalization of Conservation Values in Multicultural Education Courses through Traditional Games - Ary, Deasylina da; Busyairi, Ahmad (Universitas Negeri Semarang, 2021)
The Indonesian state is very prone to triggering conflicts and divisions because Indonesia is actually a pluralistic and heterogeneous country. The discourse on multicultural education is predicted to be able to anticipate ethnic, social and cultural conflicts that often arise in the midst of a plural-faced society, especially the implementation of multicultural education in tertiary institutions. The understanding created from multicultural education is not just a theory that is used as mere memorization, but can be developed into application in a multicultural-based learning process. One example of its application is through traditional games which require cultural values. Traditional games have even become a symbol of the region where each region uses traditional games as regional identities so that traditional games are a form of conservation value, namely preserving the cultural heritage of the local area. The research objectives: 1) Describe traditional games that contain conservation values in the multicultural education course for PGSD UNNES students; 2) Analyzing the conservation value contained in traditional games in multicultural education for PGSD UNNES students; 3) Analyze the achievement of internalization of conservation values in multicultural education courses for PGSD UNNES students. This study uses a qualitative research method which will be analyzed descriptively. Each traditional game imparts different conservation values depending on the play pattern. Traditional games that have been born for thousands of years are the result of ancient human cultural processes that are still thick with local wisdom values. In essence, conservation means maintaining and protecting something regularly to prevent damage and destruction by means of preservation. So that playing traditional games is a form of conservation value, namely preserving the cultural heritage of the local area.